2016
DOI: 10.1634/theoncologist.2015-0439
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of FOLFOXIRI Plus Panitumumab Followed by Evaluation for Resection in Patients With Metastatic KRAS Wild-Type Colorectal Cancer With Liver Metastases Only

Abstract: Lessons LearnedThis regimen is a viable option for patients with liver-only metastatic colorectal cancer.Enrollment criteria for future studies should include testing for the newly identified KRAS mutations.Background.Patients with liver-only metastatic colorectal cancer (mCRC) who are not candidates for potentially curative resection may become resectable with more aggressive chemotherapy regimens. In this nonrandomized trial, we evaluated folinic acid, 5-fluorouracil (5-FU), oxaliplatin, and irinotecan (FOLF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
(6 reference statements)
1
12
0
Order By: Relevance
“…Addition of more drugs in a chemotherapy combination requires the design of proper schedule and doses, to provide the balance between projected/received (>80%) dose intensity (DI) and treatment-related toxicity (1). This clinical balance is even more challenging to realize for intensive triplet chemotherapybased regimens that demonstrated to increase clinical outcome in fit metastatic gastro-intestinal (mGI) cancer patients (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Clinical status of the individual patient, also depending from metastatic tumor extension, is the most important variable justifying differential toxicity in individual patients.…”
Section: Introduction the Need Of Patient-related Clinical Indicator mentioning
confidence: 99%
“…Addition of more drugs in a chemotherapy combination requires the design of proper schedule and doses, to provide the balance between projected/received (>80%) dose intensity (DI) and treatment-related toxicity (1). This clinical balance is even more challenging to realize for intensive triplet chemotherapybased regimens that demonstrated to increase clinical outcome in fit metastatic gastro-intestinal (mGI) cancer patients (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Clinical status of the individual patient, also depending from metastatic tumor extension, is the most important variable justifying differential toxicity in individual patients.…”
Section: Introduction the Need Of Patient-related Clinical Indicator mentioning
confidence: 99%
“…[14][15][16][17] A phase II trial in 37 KRAS/ NRAS/HRAS/BRAF wild-type patients evaluated PAN addiction to modified FOLFOXIRI, with an ORR of 60-89%, R0 resection rate of 35%, median PFS of 11.3 and 13.3 months, respectively. 18,19 The high discontinuation rate of started treatment (48%) due to LT, mainly characterized by diarrhea associated with asthenia, confirmed that individual patient toxicity was the main limitation to the use of intensive schedules associating triplet chemotherapy and anti-EGFR-targeted agents in clinical practice. BEV addiction to FOLFOXIRI in a randomized phase III TRIBE trial reported increased clinical outcomes also in wild-type KRAS/NRAS/ BRAF patients.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the present study confirmed the need of proper selection of fit patients and evaluation of toxicity. [14][15][16][17][18][19] Different schedules of CET addition to triplet chemotherapy, chrono-IFLO, ERBIRINOX, FOLFOXIRI have been proposed, and reported a high activity (ORR 70-83%), and liver resection rate >60%. [14][15][16][17] A phase II trial in 37 KRAS/ NRAS/HRAS/BRAF wild-type patients evaluated PAN addiction to modified FOLFOXIRI, with an ORR of 60-89%, R0 resection rate of 35%, median PFS of 11.3 and 13.3 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations